ChemInform Abstract: The Invention of Immersion Ultramicroscopy in 1912 — The Birth of Nanotechnology?. Issue 10 (7th March 2013) - Mappes, Timo; Jahr, Norbert; Csaki, Andrea; Vogler, Nadine; Popp, Juergen; Fritzsche, Wolfgang
Abstract Review: [43 refs.]